2016
DOI: 10.1094/mpmi-07-16-0134-r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Low-Strigolactone Germplasm in Pea (Pisum sativum L.) Resistant to Crenate Broomrape (Orobanche crenata Forsk.)

Abstract: Crenate broomrape (Orobanche crenata Forsk.) is a devastating parasitic weed threatening the cultivation of legumes around the Mediterranean and in the Middle East. So far, only moderate levels of resistance were reported to occur in pea (Pisum sativum L.) natural germplasm, and most commercial cultivars are prone to severe infestation. Here, we describe the selection of a pea line highly resistant to O. crenata, following the screening of local genetic resources. Time series observations show that delayed eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 24 publications
0
56
0
Order By: Relevance
“…Subsequent profiling of root exudates using untargeted metabolomics (e.g., gas chromatography‐mass spectrometry; Zhang, Sun, Wang, Han, & Wang, ) will enable the identification of key metabolites or exudate profiles significantly associated with disease resistance. Pavan et al () found a pea cultivar highly resistant to broomrape infection and evidenced a reduced exudation of strigolactones as the explanation for resistance. However, strigolactones are also of great importance for AM symbiosis and care must be taken before such a selection target is chosen to avoid trade‐offs (Bakker et al, ).…”
Section: Integrating the Microbiome To Improve Resistance Against Biomentioning
confidence: 99%
“…Subsequent profiling of root exudates using untargeted metabolomics (e.g., gas chromatography‐mass spectrometry; Zhang, Sun, Wang, Han, & Wang, ) will enable the identification of key metabolites or exudate profiles significantly associated with disease resistance. Pavan et al () found a pea cultivar highly resistant to broomrape infection and evidenced a reduced exudation of strigolactones as the explanation for resistance. However, strigolactones are also of great importance for AM symbiosis and care must be taken before such a selection target is chosen to avoid trade‐offs (Bakker et al, ).…”
Section: Integrating the Microbiome To Improve Resistance Against Biomentioning
confidence: 99%
“…Recently, a highly O. crenata-resistant pea line, named ROR12, was identified [86,87]. The resistance mechanism might involve the low induction of germination due to reduced secretion of SLs.…”
Section: Pea (Pisum Sativum)mentioning
confidence: 99%
“…The resistance mechanism might involve the low induction of germination due to reduced secretion of SLs. The reduction of SL did not affect the yield of ROR12 [86,87]. The resistance of ROR12 is controlled by one or a few major genes localized on the pea linkage group 3 [86].…”
Section: Pea (Pisum Sativum)mentioning
confidence: 99%
“…showed that there is genetic variation in faba bean ( Vicia faba ) for broomrape germination stimulant production, offering the possibility to select for this trait in breeding programs. Similarly, Pavan et al . described the selection of a pea line ( Pisum sativum ), resistant to the parasitic weed Orobanche crenata through lower production of strigolactones.…”
Section: Exploitation Of Belowground Signaling In Agriculturementioning
confidence: 99%
“…Fernández-Aparicio et al 107 showed that there is genetic variation in faba bean (Vicia faba) for broomrape germination stimulant production, offering the possibility to select for this trait in breeding programs. Similarly, Pavan et al 115 described the selection of a pea line (Pisum sativum), resistant to the parasitic weed Orobanche crenata through lower production of strigolactones. Although a lower production of strigolactones seems to be an advantage in these specific contexts, tomato lines in which strigolactone biosynthesis was reduced through an RNAi strategy displayed severely reduced stem height and increased shoot branching due to the reduced hormonal control by strigolactones, making this an unsuitable strategy for resistance breeding.…”
Section: Exploitation Of Belowground Signaling In Agriculturementioning
confidence: 99%